tanh-1x Derivative examples Example #1 f(x) =x3+5x2+x+8 f '(x) = 3x2+2⋅5x+1+0 = 3x2+10x+1 Example #2 f(x) = sin(3x2) When applying the chain rule: f '(x) = cos(3x2) ⋅ [3x2]' = cos(3x2) ⋅ 6x ...
Derivative of Composite Function: If we have a composition of trigonometric and inverse trigonometric functions (sayT(I(x))), then its derivative is evaluated by applying the chain rule as shown below. dT(I(x))dx×d(I(x))d(I(x))=dT(I(x))d(I(x))⋅d(I(x))dx=T′(I(x))...
Find the derivative of f(x) = (3x)^2 * (2x + 1)^3. Find the derivative of f(x) = cos^3 x a) 3x^2 sin x b) cos(3x^2) c) 3cos^2 x Find the derivative of x^3-3x^2. Find derivative of 3x^2 +9x . Find the derivative of g(x) = 3x^2 + 5x - 2. ...
•tan(x)—tangent •cot(x)—cotangent •arcsin(x)—arcsine •arccos(x)—arccosine •arctan(x)—arctangent •arccot(x)—arccotangent •sinh(x)—hyperbolic sine •cosh(x)—hyperbolic cosine •tanh(x)—hyperbolic tangent ...
Derivative function: Enter an original function (that is, the function to be derived), then set the variable to be derived and the order of the derivative, and click the "Next" button to obtain the derivative function of the corresponding order of the function. ...
Find the derivative 1) f(x) = \frac {e^x}{x} 2) f(x) = In x Find the derivative of the function by using the Quotient Rule. \frac {(x^5+1)}{x^4} Find the derivative of f(x) = \sqrt x at x = \frac {1}{144} ...
Fig. 3. Absolute value of function represents in an Eq. (51) in 2-dimensional, 3-dimensional as well as contour plots at ɛΥ=1;θ=0.1;ϑ=1;p=1;q=1;τ=1;ɛ=1;A=1;d=3 and −3<x<3 in two-Dimensional when α=1, Blue graph when t=0, Orange graph when t=1, Gr...
Find the derivative of the function: f(x)=\frac{x^3-3x^2+2}{x^2} Find The First Derivative \sqrt [4] {3+\sec (2t))^5 \sqrt [3]{3x^3+5\sqrt{x (\ln x)^3 (3x^4-5\sqrt{5x} (1+(+(1+x^2)^2)^2)^2 Find the indicated derivative of the fun...
The Derivative of the oftanh(x)and the Chain Rule: The derivative oftanh(x)is: ddxtanh(x)=sech2(x) The Chain Rule: The chain rule is utilized to differentiate composite functions. Ify=f(u), the chain rule applies whenu=g(x), and thereforey=f(g(x)). The derivative ...
Answer to: Find the derivative of the function. f\left( x \right) = {{{e^x} + 1} \over {{e^x} - 1}} By signing up, you'll get thousands of...